1965
DOI: 10.1017/s0022172400045381
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the pathogenesis of rinderpest in experimental cattle: IV. Proliferation of the virus following contact infection

Abstract: Cattle were infected with rinderpest virus by housing them for 24 hr. in stalls containing donor animals which had been reacting to the disease for 3–5 days. They were then transferred to individual clean stalls and killed on the 2nd to 10th days following first exposure. Various tissues were collected, particularly those of the upper and lower respiratory tracts, and their virus content was estimated in calf-kidney tissue cultures.Virus was recovered from 15 of 35 animals tested and in eight of these generali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1968
1968
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 6 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…The primary establishment of virus in the bronchial mucosa and associated lymph nodes of two pigs, with or without the involvement of the retropharyngeal route, suggests that infection by aerosols of small particle size can probably occur via the lower respiratory tract. This could be an alternative route of natural infection, as shown already for rabbit-pox (Bedson & IDuckworth, 1963) and rinderpest in cattle (Taylor et al 1965). It is necessary to observe, however, that transmission of ASFV by expired air could not be demonstrated by Montgomery (1921), even over a distance as short as 6 in.…”
Section: Discussionmentioning
confidence: 86%
“…The primary establishment of virus in the bronchial mucosa and associated lymph nodes of two pigs, with or without the involvement of the retropharyngeal route, suggests that infection by aerosols of small particle size can probably occur via the lower respiratory tract. This could be an alternative route of natural infection, as shown already for rabbit-pox (Bedson & IDuckworth, 1963) and rinderpest in cattle (Taylor et al 1965). It is necessary to observe, however, that transmission of ASFV by expired air could not be demonstrated by Montgomery (1921), even over a distance as short as 6 in.…”
Section: Discussionmentioning
confidence: 86%
“…Experimental studies with other strains of RPV have also shown that whilst morbidity rates are often very high, mortality rates can vary between 30 and 90 % depending on the infecting strain (Taylor, 1986). It is accepted that correlates of pathogenicity are poorly understood for the morbilliviruses with both immune status of the host and genetic background of the infecting virus playing roles in the outcome of infection (Taylor et al, 1965;Taylor, 1986;Wamwayi et al, 1995). Using this approach with the virulent virus showed that inclusion of a heterologous gene between the P and M genes is tolerated and that the pathogenic potential of the resultant virus is comparable to that of the wild-type parent.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, PCR analysis will always be more sensitive. Historic experiments with greater numbers of animals have shown that the infection is not 100 % fatal and that some animals that develop severe disease may still clear the virus and go on to convalesce (Taylor et al, 1965;Taylor, 1986;Wamwayi et al, 1995). Studies with greater numbers of animals would be needed to determine if the rate of virus clearance is related to convalescence in cattle infected with this virus.…”
Section: Discussionmentioning
confidence: 99%